2014
DOI: 10.1002/lary.24527
|View full text |Cite
|
Sign up to set email alerts
|

Snoring and carotid artery intima‐media thickness

Abstract: 3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Self-reported snoring has been shown to be correlated to changes in arterial wall morphology; a few studies evaluate the presence of carotid artery IMT in a population of snorers, and show a correlation between the two phenomena [29,30].…”
Section: Discussionmentioning
confidence: 97%
“…Self-reported snoring has been shown to be correlated to changes in arterial wall morphology; a few studies evaluate the presence of carotid artery IMT in a population of snorers, and show a correlation between the two phenomena [29,30].…”
Section: Discussionmentioning
confidence: 97%
“…In a study of snorers and nonsnorers with only mild, nonhypoxic obstructive sleep apnea (OSA) syndrome, in which patients underwent polysomnography with quantification of snoring, heavy snoring was significantly associated with carotid atherosclerosis but not with femoral atherosclerosis . A previous study showed a relationship between primary snoring and intima‐media thickening of the carotid artery . Patients who identified themselves as snoring all of the time or most of the time in the past 4 weeks were found to have increased intima‐media thickening along several points of the carotid artery.…”
Section: Introductionmentioning
confidence: 88%
“…et al (2011) проведено первое экспериментальное исследование, в котором показано, что вибрация вызывает эндотелиальную дисфункцию в каротидных артериях, чем и объяс няется развитие каротидного атеросклероза у лиц с храпом [42]. С тех пор гипотеза, что храп являет ся потенциальным фактором повреждения артери альной стенки и прогрессирования атеросклероза каротидных артерий, продолжает активно изучать ся [43][44][45].…”
Section: дискуссииunclassified